Distinct clinical and immunological profiles of patients with evidence of SARS-CoV-2 infection in sub-Saharan Africa - Ben Morton (Nature Portfolio, 2021)
Clinical management of COVID-19 in resource-poor settings has distinct challenges and detailed patient characterisation is needed. Here, the authors describe the clinical and immunological profiles of patients at a hospital in Malawi with confirmed and suspected COVID-19.